Comparison of Subungual Glomus Tumours in Terms of Nail Aesthetics and Recurrence According to Size and Location in the Germinal or Sterile Matrix - Orman, Osman; Onal, Ayberk; Baydar, Mehmet; Sencan, Ayse; Özkan, Bilge; Öztürk, Kahraman (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2022)
Purpose The aim of this retrospective study was to investigate the effect of subungual glomus tumour size and localization in the germinal or sterile matrix on tumour recurrence and aesthetic outcomes.Patients and Methods From 35 patients who underwent surgery for a subungual glomus tumour between February 2013 and February 2020, 26 patients – 17 women and 9 men – with 27 subungual glomus tumours fulfilled the inclusion criteria. The average age was 37.3 (22–58) years. According to the patients’ surgical notes and preoperative magnetic resonance images 14 tumours were located in the sterile, 13 in the germinal matrix, and the mean size of the glomus tumours located in the germinal matrix was 4.9±1.7 mm, in the sterile matrix 3.6±1.0 mm. At the postoperative 12th month follow-up visit nail aesthetic was evaluated objectively according to Zook’s fingernail appearance scoring. In addition, patients were asked to evaluate the pain and nail appearance in the involved finger by VAS (Visual Analog Scale 0–10). Patients who experienced recurrence were noted.Results No significant Zook’s fingernail appearance score differences were observed between germinal and sterile matrix groups (p=0.097). Comparison of VAS score for pain and VAS score for nail appearance between the two groups also yielded similar values (p=0.449 and 0.395, respectively). The recurrence rate was similar at both locations (p=0.557) with 3 recurrences in the germinal, and 2 in the sterile matrix group. There was no relation between tumour size, Zook’s fingernail appearance score (p=0.874) and recurrence (p=0.784). The observed germinal matrix glomus tumours were significantly larger than the sterile matrix tumours (p=0.031).Conclusion Neither subungual glomus tumour size nor localization in the germinal or sterile matrices has different effects on nail appearance and recurrence.
Keywords: Subungual glomus tumour; germinal matrix; sterile matrix; recurrence rate; fingernail appearance